Analysis Industrial Profile Of Coconut Sugar, The Development Prospect, The Development Prospect,In The Village Kabaena The Regency Of Bombana - muhrifa, muhrifa; Rianda, La; Herdhiansyah, Dhian (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
This study aims to determine the profile of the coconut sugar industry and the prospects for developing the coconut sugar industry. The data were processed using qualitative analysis to determine the profile of the coconut sugar industry, while to see the prospects used the SWOT analysis method. The population in this study were all coconut sugar business owners. The profiles of the coconut sugar industry are labor, raw materials, capital, length of business, and income. The amount of raw materials needed in one year is 4536. The coconut sugar industry workers use family services, namely their husbands and their children, namely 3-5 people. Coconut sugar entrepreneurs carry out their profession in 5-10 years. Meanwhile, the highest income in the coconut sugar industry was in 2018, namely IDR 5,920,000 with an average of IDR 740,000 per month. Based on the observation that the prospect of the coconut industry is good in terms of income, by using the calculation of Net Income, Gross Income, and R / C analysis, it is found that the coconut sugar business can provide more benefits for the processors and this business is good to run for the future.